Modulational instability in salerno model - Umarov, Bakhram; Abdelaziz, Benseghir; Messikh, Azeddin (INSI Publications, 2011)
We investigate the properties of modulational instability in the Salerno equation in quasione dimension in Bose-Einstein condensate (BEC). We analyze the regions of modulational instability of nonlinear plane waves and determine the conditions of its existence in BEC.